Extended Versus Intermittent Meropenem Infusion in the Treatment of Nosocomial Pneumonia: A Retrospective Single-Center Study - Dong-gon Hyun; Jarim Seo; Su Yeon Lee; Jee Hwan Ahn; Sang-Bum Hong; Chae-Man Lim; Younsuck Koh; Jin Won Huh (MDPI AG, 2023)
The efficacy of extended meropenem infusions in patients with nosocomial pneumonia is not well defined. Therefore, we compared the clinical outcomes of extended versus intermittent meropenem infusions in the treatment of nosocomial pneumonia. We performed a retrospective analysis of extended versus intermittent meropenem infusions in adult patients who had been treated for nosocomial pneumonia at a medical ICU between 1 May 2018 and 30 April 2020. The primary outcome was mortality at 14 days. Overall, 64 patients who underwent an extended infusion and 97 with an intermittent infusion were included in this study. At 14 days, 10 (15.6%) patients in the extended group and 22 (22.7%) in the intermittent group had died (adjusted hazard ratio (HR), 0.55; 95% confidence interval (CI): 0.23-1.31; p = 0.174). In the subgroup analysis, significant differences in mortality at day 14 were observed in patients following empirical treatment with meropenem (adjusted HR, 0.17; 95% CI: 0.03-0.96; p = 0.045) and in Gram-negative pathogens identified by blood or sputum cultures (adjusted HR, 0.01; 95% CI: 0.01-0.83; p = 0.033). Extended infusion of meropenem compared with intermittent infusion as a treatment option for nosocomial pneumonia may have a potential advantage in specific populations.